Music Education and Youth Empowerment: A Conceptual Clarification - Abiogu, G. C.; Mbaji, I. N.; Adeogun, A. O. (Scientific Research, 2015)
This paper is a conceptual clarification of the nexus between music education and youth empowerment. It is also an exposition of how music education can be utilized for the empowerment of the Nigerian youths with a brief incursion into the meaning of education and its need for national development. The paper considers music education as a performance art which involves unique educational activities designed to enable the youths to achieve self-realization and life adjustment in the society. The conceptual clarifications touch upon some philosophical principles which guide music education in its application as a tool of empowerment of youths and how Nigerian government can borrow a leaf from some of the African countries who partner with non-governmental organizations (NGOs) such as the Music Crossroad International (MCI) organization to empower their youths and communities. Through the creation of such musical opportunities through partnerships by such countries, implications for Nigeria are drawn with recommendations and conclusions.
Keywords: Conceptual Clarifications; Music Education; Performance Art; Philosophical Principles; Educational Activities; Youths Empowerment; Self-Realization; Musical Opportunities and Life Adjustment in the Society